Association of exposure to manganese and iron with relaxation rates R1 and R2- magnetic resonance imaging results from the WELDOX II study - Pesch, Beate; Dydak, Ulrike; Lotz, Anne; Casjens, Swaantje; Quetscher, Clara; Lehnert, Martin; Abramowski, Jessica; Stewig, Christoph; Yeh, Chien-Lin; Weiss, Tobias; van Thriel, Christoph; Herrmann, Lennard; et al. (Neurotoxicology (Park Forest South), 2018)
•Blood manganese was associated with the relaxation rate R1 in the globus pallidus.•Serum ferritin was a predictor of the relaxation rate R1 in the globus pallidus.•Former welders had no increased relaxation rate R1 compared to controls.•Respirable Mn above 100μg/m3 was associated with stronger R1 signals in welders. Magnetic resonance imaging is a non-invasive method that allows the indirect quantification of manganese (Mn) and iron (Fe) accumulation in the brain due to their paramagnetic features. The WELDOX II study aimed to explore the influence of airborne and systemic exposure to Mn and Fe on the brain deposition using the relaxation rates R1 and R2* as biomarkers of metal accumulation in regions of interest in 161 men, including active and former welders. We obtained data on the relaxation rates R1 and R2* in regions that included structures within the globus pallidus (GP), substantia nigra (SN), and white matter of the frontal lobe (FL) of both hemispheres, as well as Mn in whole blood (MnB), and serum ferritin (SF). The study subjects, all male, included 48 active and 20 former welders, 41 patients with Parkinson's disease (PD), 13 patients with hemochromatosis (HC), and 39 controls. Respirable Mn and Fe were measured during a working shift for welders. Mixed regression models were applied to estimate the effects of MnB and SF on R1 and R2*. Furthermore, we estimated the influence of airborne Mn and Fe on the relaxation rates in active welders. MnB and SF were significant predictors of R1 but not of R2* in the GP, and were marginally associated with R1 in the SN (SF) and FL (MnB). Being a welder or suffering from PD or HC elicited no additional group effect on R1 or R2* beyond the effects of MnB and SF. In active welders, shift concentrations of respirable Mn>100μg/m3 were associated with stronger R1 signals in the GP. In addition to the effects of MnB and SF, the welding technique had no further influence on R1. MnB and SF were significant predictors of R1 but not of R2*, indicative of metal accumulation, especially in the GP. Also, high airborne Mn concentration was associated with higher R1 signals in this brain region. The negative results obtained for being a welder or for the techniques with higher exposure to ultrafine particles when the blood-borne concentration was included into the models indicate that airborne exposure to Mn may act mainly through MnB.